Level of education and risk for self-reported cardiovascular disease - The Tromsø Study, 1994-2016 - Cathro, Celina Janene (UiT Norges arktiske universitet, 2021)
Introduction & Background: Cardiovascular disease (CVD) is one of the most prevalent non-communicable diseases (NCDs) globally. In 2018, CVD claimed 12,091 lives in Norway, and between 2005-2016 approximately 21% of the Norwegian population were administered therapeutic drugs to treat or prevent CVD. The World Health Organization has created a target to reduce NCD deaths by 33% between 2010-2030 for those under age 70. Although Norway is well on its way to achieving this goal due to advances in medical technologies and reductions in certain risk factors, it is expected that in the coming decades CVD prevalence will increase as the population ages. In Norway, education is tuition free, and healthcare is covered by a single-payer system. Yet, health inequalities are still large within the country, especially between populations with different educational levels. Previous research has shown education to be a risk factor for CVD. Therefore, it seems prudent that we conduct more research on the relationship between educational attainment and CVD in Norway. The Norwegian government could then use this research to implement programs to help lessen the burden of CVD on the healthcare system as well as on individuals in the future. Objective: To investigate the association between educational attainment and self-reported CVD (heart attack, stroke, and angina) in Tromsø, Norway. Materials & Methods: This prospective cohort study included 12,400 adults from Tromsø, Norway enrolled in the Tromsø 4 and 7 studies between 1994-2016. Exposure information was collected during Tromsø 4 via onsite measurements and questionnaires. Outcome information was collected during Tromsø 7 using questionnaires. Logistic regression was used to obtain odds ratios (OR) and 95% confidence intervals (CI). Results: The OR for CVD was 0.84 (95% CI: 0.80-0.88) and 0.96 (95% CI: 0.92-1.01) for the crude and multivariate models, respectively. In the crude and multivariate models for heart attack, the OR was 0.82 (95% CI: 0.77-0.87) and 0.97 ...